EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN TEBU PADA LAHAN KARST FORMASI WONOSARI (TMWL) KECAMATAN GEDANGAN KABUPATEN MALANG - Pramudito Kartiko Dumipto; Mochtar Lutfi Rayes; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Karst landform has different soil properties than the others land which are high clay content, low water holding capacity, relatively low nutrient availability, and in some areas it has a shallow soil that can impact the suitability of sugarcane productivity. It is necessary to analyze the suitability classes of sugarcane on karst landform based on productivity and make the criteria of sugarcane on karst landform. Research was conducted in Gedangan District, Malang Regency, East Java Province, Indonesia with survey method (13 land map unit) with 38 minipits and 8 soil profil as typical pedon. The modification using boundary line method by multiple regression with stepwise method which has a value of R² ³ 0,5 and percentage production class. Land suitability at study area before modification has class S3 (Marginally Suitable) and N (Not Suitable). Boundary line method results land characteristics that significantly correlate with production (organic carbon, total N, available P, exchangeable K, soil depth and slope). The boundary line method results class S2 (Moderately Suitable), S3 and N with accuration 75%. The modification with percentage production class was done (organic carbon, total N, exchangeable K, and slope) and results class S1(Highly Suitable), S2, S3, and N with accuration 91%.